Pengaruh Penggunaan Gadget Terhadap Kesejahteraan Sosial-Emosional Anak Usia Dini - Nitha Andinie Martha; Taopik Rahmat; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to explore the effect of gadget use on the social-emotional condition of early childhood. Nowadays, gadgets have become a common part of children's daily activities. While they can provide certain benefits, excessive use may affect children's emotional development and social skills. This research used a quantitative approach with a survey method. Data were collected through questionnaires filled out by parents and observations conducted by teachers in a PAUD setting. The findings indicate that children who frequently use gadgets tend to have more difficulty interacting with others and managing their emotions compared to those with more limited usage. These results suggest that gadget use is related to children's social-emotional condition. Therefore, guidance and supervision from parents and teachers are needed to ensure that gadget use remains balanced and does not negatively impact children's development